MENAHAN ATAU MENEKAN KEKEBALAN (IMUNOSUPRESI) UNTUK PENCANGKOKAN GINJAL (Bagian II) - Suprapto Ma’at (INDONESIAN JOURNAL OF CLINICAL PATHOLOGY AND MEDICAL LABORATORY, 2008)
Renal transplantation is the treatment of choice for most patients with end stage renal disease. Most of the time, transplantationrejection is immunological mediated. Both T cells and circulating antibodies are induced against allograft. Successful organtransplantation requires the use of immunosuppressive drugs to prevent the host’s immune system from rejecting the transplanted organ.The development of immunosuppressive drugs is the key to successful allograft function Immunosuppressive agents are used for induction(intense immunosuppressant in the initial days after transplantation), maintenance and reversal of established rejection. This reviewfocuses on agents that are either approved or in phase 2 or phase 3 trials in kidney transplantation.